2009
DOI: 10.1007/s00296-009-0883-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL-23 and IL-17 and effect of IL-23 on IL-17 production in ankylosing spondylitis

Abstract: The objective of this study was to investigate the expression of IL-23 and IL-17 and the influence of IL-23 on IL-17 production in ankylosing spondylitis (AS) patients. IL-23 and IL-17 levels in the serum and supernatants of cultured peripheral blood mononuclear cells (PBMCs) were determined by ELISA. IL-23p19 mRNA expression in PBMCs were analyzed using RT-PCR. The patients with AS at active stage showed elevated levels of IL-23 and IL-17 in the serum and supernatants of cultured PBMCs. A higher expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 27 publications
6
52
1
2
Order By: Relevance
“…In humans, IL-23 is over-expressed in clinical samples of psoriasis (Lee et al 2004), CD (Schmidt et al 2005) and ankylosing spondylitis (Wang et al 2009). Becker et al (2006) showed that blocking the p40 subunit of either IL-12 or IL-23, but not blocking the p19 unit (Ferguson et al 2010), was effective in reducing disease symptoms in chemically-induced colitis models.…”
Section: Il-23 (Interleukin Il-23)mentioning
confidence: 99%
“…In humans, IL-23 is over-expressed in clinical samples of psoriasis (Lee et al 2004), CD (Schmidt et al 2005) and ankylosing spondylitis (Wang et al 2009). Becker et al (2006) showed that blocking the p40 subunit of either IL-12 or IL-23, but not blocking the p19 unit (Ferguson et al 2010), was effective in reducing disease symptoms in chemically-induced colitis models.…”
Section: Il-23 (Interleukin Il-23)mentioning
confidence: 99%
“…Moreover, studies in humans show that production of and sensitivity to IL-23 are increased and IL-23-responsive cells are expanded in many forms of SpA (9,(12)(13)(14), together strongly implicating IL-23 and the cells upon which it acts in the pathogenesis of SpA and IBD. In support of these findings, overexpression of IL-23 by hepatic injection of Il23 minicircles was recently shown to be sufficient to drive enthesitis and aortitis in mice through IL-23Rϩ innate lymphoid enthesealresident cells in a process involving IL-22 and IL-17 (15).…”
Section: Il12bmentioning
confidence: 99%
“…Moreover, for the first time, a higher expression of IL-23 p19 mRNA in PBMC of AS patients as well as enhanced production of IL-17 in the supernatants of PBMC cultured in the presence of recombinant IL-23 was found by Wang et al [1]. Previous studies did not demonstrate elevated levels of p40 IL-23 in the serum of AS patients, compared with controls, whereas, in some of them, synovial fluid levels were higher than serum levels [7].…”
Section: Sirmentioning
confidence: 76%
“…According to the results of Wang et al [1], one may speculate that p19 IL-23 blockade may be even more efficacious, and may represent a new therapeutic pathway in AS.…”
Section: Sirmentioning
confidence: 99%
See 1 more Smart Citation